Developing The Efficiency Of Indonesian Students For Composing The Sentence Based On Psychological Aspects - Mufidah, Nuril ((???????? ) EL-THUMUHAT, 2018)
One of difficulty of teaching Arabic language especially in the beginner class is most of students have never studied Arabic before, even some students who can not read or write Arabic letters correctly. In Arabic there are two types of sentences, noun sentence and verbal sentence. The difficulties faced by low-class is to understand and produce verbal sentences because the verb form of Indonesian language is the noun form sentence.             The purpose of this study was to observe the effect of chain exercises based on psychological aspects that begin with noun sentence; to develop in creating the sentence for Indonesian students.             This research is experimental in its implementation consists of four steps: (1) planning (2) experiment (3) observations and (4) assessment. The population is the student of  intensive class of Arabic in Universitas Islam Negeri Maulana Malik Ibrahim Malang. While the instruments used in this study is the observation and examination.             The results of this study indicate that chain exercises based on psychological aspects can improve students’s skill for creating the sentence. Composing the sentence based on psychological aspects helps students to avoid scared of learning Arabic and monotony.